From Engagement to Concerns: Social Media Use Among a Sample of Australian Public Health Professionals - McCausland, Kahlia; Tazrin, Zannatul; Leavy, Justine; Freeman, B.; Wolf, Katharina; Leaver, Tama; Chih, Jun; Mullan, Barbara; Girdler, Sonya; Jancey, Jonine (Australian Health Promotion Association, 2025)
Issue Addressed Social media plays a crucial and diverse role in health promotion and public health. However, professionals often cite various concerns and a lack of knowledge of how to use it effectively. This study aimed to explore the use of social media by Australian health promotion and public health professionals.